2019
DOI: 10.1042/bsr20190867
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and psoriasis

Abstract: Psoriasis is caused by a complex interplay among the immune system, genetic background, autoantigens, and environmental factors. Recent studies have demonstrated that patients with psoriasis have a significantly higher serum homocysteine (Hcy) level and a higher prevalence of hyperhomocysteinaemia (HHcy). Insufficiency of folic acid and vitamin B12 can be a cause of HHcy in psoriasis. Hcy may promote the immuno-inflammatory process in the pathogenesis of psoriasis by activating Th1 and Th17 cells and neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 141 publications
1
35
0
3
Order By: Relevance
“…For example, in psoriatic skin, miR-203 is reported to regulate excessive proliferation and differentiation of keratinocytes through inhibition of the suppressor of cytokine signaling 3 and regulation of cytokine signaling [17]. More importantly, psoriatic arthritis is a major comorbidity of psoriasis, and the reported proportion of psoriatic arthritis among psoriatic patients ranges from 7 to 26% [18]. Previous studies have shown that miR-221-3p is closely associated with psoriatic arthritis [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in psoriatic skin, miR-203 is reported to regulate excessive proliferation and differentiation of keratinocytes through inhibition of the suppressor of cytokine signaling 3 and regulation of cytokine signaling [17]. More importantly, psoriatic arthritis is a major comorbidity of psoriasis, and the reported proportion of psoriatic arthritis among psoriatic patients ranges from 7 to 26% [18]. Previous studies have shown that miR-221-3p is closely associated with psoriatic arthritis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is a skin disease associated with a multifactorial profile, as immunological status, environment, and genetic patterns [61][62][63][64][65][66][67]. Nutrition holds a key role as different aliments interact for the development of psoriasis depicted in several studies implicating gut microbiota as well [66][67][68][69][70][71]. The Mediterranean diet (MD) seems to have a positive healthful impact in the development of psoriasis [72,73].…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…Methotrexate (MTX) is a folate antagonist that inhibits the activity of dihydrofolate reductase activity and is one of the most widely used synthetic drugs in PsA treatment. Unfortunately, its effects on the cardiovascular are diametrically opposed, and, eventually, its prolonged administration may increase serum homocysteine level ( 83 ) and cardiovascular risk in patients with previous hyperhomocysteinemia ( 84 ). Fortunately, increasing homocysteine levels by MTZ can be prevented with folic acid administration ( 83 ) while keeping the anti-inflammatory properties that reduce cardiovascular risk.…”
Section: Relationships and Change In Therapeuticsmentioning
confidence: 99%